Life on Mars : tales from the new frontier : an original science fiction anthology - Strahan, Jonathan (New York : Viking, 2011)
A collection of twelve original stories that explore the possibility of being able to travel to and live on Mars.
Attlee and the long walk / by Kage Baker -- The old man and the Martian Sea / by Alastair Reynolds -- Wahala / by Nnedi Okorafor -- On Chryse Plain / by Stephen Baxter -- First principle / by Nancy Kress -- Martian chronicles / by Cory Doctorow -- Goodnight moons / by Ellen Klages -- The taste of promises / by Rachel Swirsky -- Digging / by Ian McDonald -- LARP on Mars / by Chris Roberson -- Martian heart / by John Barnes -- Discovering life / by Kim Stanley Robinson.
012-up.
Keywords: Mars (Planet) -- Juvenile fiction; Science fiction; Children's stories; Mars (Planet) -- Fiction; Science fiction; Short stories